Effect of carbon materials with different nano-iron oxide loadings on aerobic granular sludge systems - Deng, Kai-Peng (Environmental technology, 2025)
This study investigated iron oxide-loaded powdered activated carbon (FONP-PAC) with varying Fe/C ratios (FC1 in S1, FC2 in S2) in aerobic granular sludge (AGS) systems. S2 achieved the fastest sludge growth, reaching 1106 μm by day 80 (87.14% larger than control S0). During stable operation, S2 exhibited superior pollutant removal: 95.96% COD, 100% NH4+-N, and 79.53% TN removal, alongside the highest aerobic denitrification rate (9.93 mg·gVSS⁻¹·h⁻¹, 71.68% above S0). Comparatively, S1 showed slightly lower efficiencies (94.20% COD, 100% NH4+-N, 71.50% TN) and denitrification activity (8.35 mg·gVSS⁻¹·h⁻¹). Microbial analysis revealed enriched Bacteroidota phyla and sustained Zoogloea genus abundance in FONP-PAC reactors. Higher iron oxide loading enhanced interspecies electron transfer, accelerating granule growth and nitrogen removal. Larger granules in S2 promoted stratified microbial niches, improving oxygen gradient-dependent processes like simultaneous nitrification-denitrification. These findings demonstrate that optimized FONP-PAC dosing strengthens sludge structure and metabolic synergy, achieving dual benefits of rapid granulation and high-efficiency nutrient removal through physicochemical-microbial interactions. The study provides insights into nano-material mediated AGS enhancement for wastewater treatment optimization.HighlightsThe threshold effect of nano-iron oxide loading on the granulation rate of AGS (Anaerobic Granular Sludge) was revealed.The mechanism by which FONP-PAC (Functionalized Oxide Nanoparticles-Polymeric Aluminum Chloride) promotes interspecies electron transfer through a conductive network was elucidatedA strategy for the targeted enrichment of Thauera and Zoogloea by the material was proposed